Analisis Penggunaan Ragam Bahasa Generasi Z pada Film “Mencuri Raden Saleh” - Ahmad, Ikfina Maryam; Gunawan, Vania Indri; Rahmawati, Ilga Nur; Anggraeni, Natalia Desy (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Language growth goes hand in hand with technological advances. Generation Z, a generation born and living in the modern era, has a different communication style, such as the use of new terms, a relaxed language style, and the habit of combining Indonesian with English. This study aims to analyze how Generation Z's language variety describes their communication characteristics, and how this language can strengthen the relationship between each character in the film Mencuri Raden Saleh. In this study, the researcher used a descriptive qualitative research method approach and focused on the object of new vocabulary or slang terms, loanwords, and the typical communication style of Generation Z. This film contains many interesting things that can be studied, one of which lies in the language style used, which reflects the way young people communicate. Based on sociolinguistic theory, the social identity theory of Henri Tajfel and John Turner, and the Sapir-Whorf linguistic relativity theory, this study explains that Generation Z's language variety shows their social identity, reflects the culture of this generation, and influences the way they think, interact, and form lifestyles. In the context of Generation Z, the language style they use often shows their cultural identity and preferences, one of which is the use of slang or a relaxed way of communicating. This analysis shows that non-standard language not only functions as a means of communication, but also as a means of building character